The Impact of Playworks on Boys' and Girls' Physical Activity During Recess. (March 2015) - Bleeker, Martha; Beyler, Nicholas; James‐Burdumy, Susanne; Fortson, Jane
ABSTRACT BACKGROUND School‐based programs, such as Playworks, that guide students in organized activities during recess and make improvements to the recess play yard may lead to significant increases in physical activity—especially for girls. This study builds on past research by investigating the impact of Playworks separately for girls and boys. METHODS Twenty‐nine schools were randomly assigned to receive Playworks for 1 school year or serve as a control group. Postintervention physical activity data were collected via accelerometers and recess observations. Impacts were estimated separately for girls and boys using regression models. RESULTS Girls in Playworks schools had significantly higher accelerometer intensity counts and spent more time in vigorous physical activity than girls in control schools. No significant differences based on accelerometer data were found for boys. A significant impact was also found on the types of activities in which girls engaged during recess; girls in the treatment group were less likely than those in the control group to be sedentary and more likely to engage in jumping, tag, and playground games. CONCLUSIONS The current findings suggest that Playworks had a significant impact on some measures of girls' physical activity, but no significant impact on measures of boys' physical activity.